2011
DOI: 10.1007/s00018-011-0729-z
|View full text |Cite
|
Sign up to set email alerts
|

The functional RNA domain 5BSL3.2 within the NS5B coding sequence influences hepatitis C virus IRES-mediated translation

Abstract: Hepatitis C virus (HCV) translation is mediated by an internal ribosome entry site (IRES) located at the 5' end of the genomic RNA. The 3' untranslatable region (3'UTR) stimulates translation by the recruitment of protein factors that simultaneously bind to the 5' end of the viral genome. This leads to the formation of a macromolecular complex with a closed loop conformation, similar to that described for the captranslated mRNAs. We previously demonstrated the existence of a long range RNA-RNA interaction invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
106
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(119 citation statements)
references
References 60 publications
12
106
1
Order By: Relevance
“…In modified translation only reporter systems an antisense-LNA, complementary to both the terminal and bulge loop of SL9266, inhibited HCV IRES driven translation ∼2-fold more efficiently than for poliovirus IRES initiated translation and ∼4-fold more efficiently than m 7 G cap-dependent translation. The sub-terminal bulge loop of SL9266 and domain IIId of the HCV IRES include a six-nucleotide complementary motif (40). Their demonstrated interaction in in vitro assays has been suggested to indicate a role in modulation of translation (28,40), although we have not found evidence to support this model or interaction using SHAPE mapping and reverse genetics (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In modified translation only reporter systems an antisense-LNA, complementary to both the terminal and bulge loop of SL9266, inhibited HCV IRES driven translation ∼2-fold more efficiently than for poliovirus IRES initiated translation and ∼4-fold more efficiently than m 7 G cap-dependent translation. The sub-terminal bulge loop of SL9266 and domain IIId of the HCV IRES include a six-nucleotide complementary motif (40). Their demonstrated interaction in in vitro assays has been suggested to indicate a role in modulation of translation (28,40), although we have not found evidence to support this model or interaction using SHAPE mapping and reverse genetics (23).…”
Section: Discussionmentioning
confidence: 99%
“…The sub-terminal bulge loop of SL9266 and domain IIId of the HCV IRES include a six-nucleotide complementary motif (40). Their demonstrated interaction in in vitro assays has been suggested to indicate a role in modulation of translation (28,40), although we have not found evidence to support this model or interaction using SHAPE mapping and reverse genetics (23). The fact that blocking SL9266/PK significantly inhibits translation from both a m 7 G cap and poliovirus IRES - although to a lesser degree than from the HCV IRES - further suggests that SL9266/PK does not act on translation through a direct RNA–RNA interaction with the HCV IRES (the poliovirus IRES does not contain sequence motifs complementary to known interactions of the bulge-loop of SL9266 using either canonical or non-canonical pairing; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The stem-loop 5BSL3.2 within the CRE region forms a high-order structure involved in viral RNA translation and replication (31). Six nucleotides form base pairs between the bulge of the 5BSL3.2 stem-loop and the IIId loop of the IRES, inhibiting translation initiation (32). Conversely, mutations in 5BSL3.2 increased IRES activity supporting the existence of a functional high-order structure in the HCV genome that involves two conserved RNA motifs, one within the IRES and another in the CRE region.…”
Section: Introductionmentioning
confidence: 99%
“…These long-range interactions formed by stem-loop structures have been shown to be critical for HCV genome replication. It has been recently reported that the 5BSL3.2 CRE is involved in a long-range interaction with subdomain IIId of the 5= NTR IRES region, and the resulting interaction negatively influences the IRES-mediated translation (61,62). It is postulated that the 5BSL3.2 CRE could function as a switch modulating the translation and genome replication of the sense-stranded HCV genome (60).…”
mentioning
confidence: 99%